Synergistic Effect of Clinically Available Beta-Lactamase Inhibitors Combined with Cefiderocol against Carbapenemase-Producing Gram-Negative Organisms - Gabriele Bianco; Paolo Gaibani; Sara Comini; Matteo Boattini; Giuliana Banche; Cristina Costa; Rossana Cavallo; Patrice Nordmann (Antibiotics, 2022)
The role of β-lactamases in reduced susceptibility or resistance to cefiderocol has been supported by recent reports. The purpose of this study was to investigate the in vitro impact of clinically available β-lactamase inhibitors on cefiderocol activity against characterized carbapenemase-producing Gram-negative isolates. A collection of 39 well-characterized Gram-negative isolates obtained from various clinical sources and countries were included. Cefiderocol antimicrobial susceptibility was evaluated via reference broth microdilution. The chequerboard microdilution method and time–kill assays were used to determine the synergy of tazobactam, avibactam, vaborbactam and relebactam in combination with cefiderocol. MICs of cefiderocol presented a 4- to 256-fold reduction against Klebsiella pneumoniae carbapenemase (KPC)-producing Gram-negative isolates (predominantly K. pneumoniae) when avibactam, vaborbactam and relebactam were combined individually. Notably, the KPC-inhibitors led to a 4- to 32-fold reduction in cefiderocol MICs in the four cefiderocol-resistant KPC-producing K. pneumoniae isolates, showing restoration of cefiderocol susceptibility (MIC ≤ 2 mg/L) in ten out of twelve cases. Tazobactam led to a 4- to 64-fold decrease in cefiderocol MICs only in K. pneumoniae strains harbouring blaKPC-41, blaKPC-31, blaKPC-53 and blaKPC-66. The synergistic effect of all serine-β-lactamase inhibitors on cefiderocol activity was also shown in OXA-48-like-producing Enterobacterales strains. Conversely, a combination of β-lactamases inhibitors with cefiderocol was not synergistic with all OXA-23-like-producing strains and most metallo-β-lactamases producers. In conclusion, the addition of clinically available serine β-lactamase inhibitors to cefiderocol might represent an important development in the formulation to increase its spectrum and therapeutic efficacy, and to limit in vivo resistance emergence.